L’emploi d’expressions métalangagières : phénomènes de saillance et travail interprétatif - Blandine Pennec (Anglophonia)
This paper examines the phenomena of textual salience as well as the interpretative mechanisms linked to the use of metalinguistic expressions. It focuses on the expressions “so to speak”, “I almost said X” and “what we might call X”.Since these expressions both show a reflexive approach to one’s own discourse and point up the textual element which is targeted, they can lead the addressee to understand the targeted element as salient. The syntactic and semantic properties of the metalinguistic expressions are examined in this paper, as they explain the position of the salient element (knowing that this position depends on the metalinguistic expression used). These properties also account for the interpretation of the salient element.The purpose of this study is to determine the nature of the salience achieved and to understand the enunciative operations as well as the cognitive mechanisms involved. The study is carried out in the framework of the Theory of Enunciative Operations and includes considerations borrowed from usage-based Cognitive Linguistics.